Prototipe Robot Automated Guided Vehicle (AGV) Berbasis Dobot AI Starter - Tugino; Sudiana; Nabila Fathiatul Afia (Institut Teknologi Nasional Yogyakarta, 2023)
Modernization in the industrial sector is to replace work that is usually using a human power, to using robots as workers. This provides time and cost efficiencies for the related industry. Automated Guided Vehicle (AGV) is a robot concept that works to deliver goods from one point to another through the path that has been created. This research was conducted to make an AGV robot prototype based on the Dobot AI Starter robot which can detect the type of goods carried by color through a color sensor, then it will move with the Line Follower principle using an infrared sensor, then can deliver and lower the goods to a predetermined place based on color. The results of research experiments carried out by the robot can work properly, the robot can detect the type of color of the goods being carried and deliver to the specified unloading point of goods and then return to the pickup point of the goods.